Pelatihan Dan Workshop Pengelolaan Organisasi Mudika Paroki Santo Paulus Juanda - Daniel Tulasi; Robertus Sigit Haribowo Lukito; Lena Ellitan; Dominicus Wahyu Pradana (LPPM, Universitas Katolik Widya Mandala Surabaya, 2019)
Catholic youth (mudika) as a part of the nation's components have a very strategic role and their role is eagerly awaited to help build the Indonesian nation. During their journey, they are faced with two difficult choices according to their point of view, which are actually not things that must selected one, but can work on an ongoing basis. These options are; choose to focus on school / college only and choose to focus on school / college and also be active in the organization. In response to this, mudika requires enlightenment from other, more experienced parties (parents, teachers, lecturers or seniors) who have been involved in organizations or company.